The effects of Balanite aegyptiaca kernel cake as supplement on alloxan-induced diabetes mellitus in rats - M. S. Nadro, F. P. Samson (Journal of Applied Pharmaceutical Science, 2014)
Diabetes mellitus is one of the disease for which a satisfactory treatment is not available in modern allopathic system of medicine. Therefore, there is a need to develop newer treatment strategies of plant origin as they are known to have fewer side effects. The present study investigated the possible therapeutic effects of Balanite aegyptiaca kernel cake on certain biochemical markers in alloxan-induced diabetes mellitus in rats. Diabetes was induced in albino rats by single intraperitoneal injection of Alloxan (70mg/kg body weight). Normal diet supplemented with 10% and 20% of kernel cake of Balanites aegyptiaca were fed to diabetic rats for three weeks. The effects of the aegyptiaca kernel cake on blood glucose, albumin, urea, creatinine, total cholesterol, triglyceride and the activities of liver marker enzymes aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase were examined in the serum of control and treated groups. Supplementation of Balanites aegyptiaca kernel cake 10% and 20% to diabetic rats for Three weeks significantly reduced blood glucose (451.80 ± 5.4 to 408.60 ± 1.8), urea (429.30±1.10 to 203.40± 4.1), and creatinine (2.05±0.05 to 1.80±0.21) but increased the levels of albumin (3.14±0.07 to 3.50±0.01), and restored all marker enzymes to near normal levels. The present results showed that Balanites aegyptiaca kernel cake has an antihyperglycaemic and antihyperlipidemic effect and consequently may alleviate liver and renal damage associated with Alloxan-induced diabetes mellitus in rats.
Keywords: Alloxan, diabetes mellitus, Balanite aegyptiaca, kernel cake, supplementation.